Czynniki kształtujące wyższą umieralność mężczyzn, aniżeli kobiet w Bułgarii - Sdméonoff, Emanuel; Andréeva, Małgorzata (Wydział Prawa i Administracji UAM, 1966)
The basic source of material for this paper constitute the statistical data published by the Central Statistical Office of Bulgaria functioning at the Ministers' Council. The study of the death tables covering various observations periods between 1920 and 1962, has shown that the average life duration of men was always shorter than the life duration of women. Using an indice expressing the relation of men's death rate coefficient with that of women's coefficient it can be seen that in different periods from 1920 up to 1939 and for the age of 5 to 45 years — the said indice is almost always below the size of one, and for the age of 45 to 85 years — above one. On the other hand in the observation periods from 1946 up to 1956 the above mentioned indice is above the size of one in every age group. Today it can be already said, that in the interwar periods of observation an important influence on the size of the indice had the high death risk of women in their fertility age. After the II world war, on the other hand, great influence on the shape of the indice had death cases caused by fatal accidents. In the towns the percentages of deaths caused by fatal accidents among men of the age of 5 to 29 years oscillated between 49% and 56%, whereas among women they reached only 29%. In the rural areas the death percentages among men caused by fatal accidents were still higher. In the fifteen-year period from 1947—1962 the percentages of death due to fatal accidents have doubled in all the age groups in the men as well as women folk. There are, however, age groups of men, in which that percentage showed a fivefold increase.
Factors Determining Higher Death-Rate of Men in Comparison to Women in Bulgaria